Vpliv prostora na volilno vedenje - Uršič, Matjaž (Teorija in praksa, 2022)
The article discusses how spatial values connect to political preferences and the spatial system of Slovenia. The presented geospatial analysis provides insights into the active role played by place, informal social and political control as well as other characteristics of the territorial/cultural environment. Data were collected from eight consecutive parliamentary elections for the period 1996–2022 where the election results are observed through the division between urban and rural; more precisely, by type of settlement according to the degree of urbanisation and the index of fragmentation. The results showed on one hand that the electorates of Slovenian political parties are relatively heterogeneous, supporting the idea of the gradual development of increasingly diverse lifestyles, ways of living and the general functional mixing of urban and rural areas. On the other hand, the results concerning voting behaviour reveal that the division into more politically left-oriented urban and more right-oriented rural areas remains deeply present and fuelled by elements of localism that persist, despite some periods of fluctuation
Keywords: družbeni nadzor; politične stranke; ruralna naselja; ruralna sociologija; Slovenija; urbana naselja; Volitve